2008
DOI: 10.1111/j.1540-6229.2008.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Variation in REIT Capital Structure: The Role of Asset Liquidation Value

Abstract: We test the Shleifer-Vishny hypothesis that asset liquidation values influence both firm leverage and the choice of debt maturity. Using panel data on real estate investment trusts, we estimate a simultaneous equation model and find that firms specializing in the most (least) liquid assets use more (less) leverage and longer (shorter) maturities. The evidence also suggests that, for REITs, debt maturity and leverage are substitutes, consistent with the theory and predictions of Barclay, Marx and Smith. Copyrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
75
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 30 publications
(108 reference statements)
10
75
3
Order By: Relevance
“…8 Giambona et al (2008) used an approach similar to Johnson's to study the role of asset liquidation value. Shleifer and Vishny (1992) predicted firms with assets that retain their value in financial distress and can be easily redeployed will use higher leverage and longer maturity debt.…”
Section: Recent Literature On Corporate Governance and Capital Structurementioning
confidence: 99%
See 1 more Smart Citation
“…8 Giambona et al (2008) used an approach similar to Johnson's to study the role of asset liquidation value. Shleifer and Vishny (1992) predicted firms with assets that retain their value in financial distress and can be easily redeployed will use higher leverage and longer maturity debt.…”
Section: Recent Literature On Corporate Governance and Capital Structurementioning
confidence: 99%
“…Although limiting the sample to a single industry has the drawback of making it harder to establish the generality of the findings, we believe that for this study, there are a number of offsetting benefits. One reason for focusing on REITs is that Benmelech (2005), Benmelech et al (2005) and Giambona et al (2008) have shown that asset liquidation value is an often overlooked significant determinant of a firm's capital structure and that there are good proxies for asset liquidation value available for REITs. 5 Furthermore, REITs are well-suited for the study of agency issues related to capital structure because their tax-advantaged status, high required dividend payout, and uniform asset regulation eliminate or reduce the need to control for potentially confounding effects such as tax considerations or variations in dividend payout rates.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, externally managed REITs are associated with lower leverage and they pursue loans of shorter maturity. Our results are robust to the inclusion of other firm variables that influence debt decisions of Asian-Pacific REITs, and to alternative specifications which we model leverage and debt maturity as simultaneous decisions (Giambona et al 2008;Ghosh et al 2011;Alcock et al 2014).…”
Section: Introductionmentioning
confidence: 65%
“…Leland and Toft (1996) argue that capital structure is not a standalone choice and optimal leverage is a function of a firm's risk as well as its debt maturity. Giambona et al (2008) and Alcock et al (2014) highlight the importance of the multidimensionality of capital structure choices in the real estate industry 2 noting that, when REITs issue debt, a crucial and simultaneous decision is to determine the maturity term of the debt contracts. Research in debt maturity choices has found some determinants for maturity in REIT debts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation